Prostate Biopsy after Abdominoperineal Resection: A Diagnostic Challenge. Issue 3 (July 2013) - Morlacco, Alessandro; Bierti, Sergio; Abbinante, Maria; Frea, Bruno; Crivellaro, Simone
Prostate biopsy in patients who underwent abdominoperineal resection (APR) of the rectum is commonly considered a technical challenge even for experienced urologists, although tissue diagnosis is essential in prostate cancer management. Transperitoneal, transperineal and transgluteal approaches have been reported, under US, CT or MRI guidance. Transperineal biopsy seems to be the safest and most cost-effective technique. At our institution we developed a modified transperineal biopsy approach with combined transperineal and suprapubic US guidance. Here we report the cases of two patients who came to our institution for PSA raise years after APR procedure, describing in detail the modified transperineal technique and the results of tissue sampling.